Quo Vadis Legal Protection for Children Recruited as Child Soldiers in Areas of Armed Conflict in the Context of International Law - Suryokumoro, Herman; Ikaningtyas, Ikaningtyas; Muafi, Mochamad (Faculty of Law, Universitas Brawijaya, 2020)
The objective of this research is to analyze legal protection of children who become child soldiers in areas experiencing armed conflict. Various international legal instruments that regulate the prevention, protection, and even enforcement for violators of certain international legal instruments on the recruitment of children as child soldiers have actually not been able to reduce the number of children who become victims in armed conflict, particularly those who are directly involved as child soldiers. This is because normatively, there are still some problems on the uniformity of definition of children age as well as the classic problem of the binding power of all related international legal instruments, being whether or not they create compulsory obligation. Legal protection for children who are recruited as child soldiers must be implemented because in the perspective of human rights, the right of children to live safely and comfortably for their proper growth and development is a fundamental right that must be complied by all states (ius cogens). If a state does not grant protection, and even allows children to be directly involved in armed conflict, then international legal sanctions may be imposed.